Exploring Hypertension Knowledge and Identifying Determinants of Inadequate Knowledge Among Non-Hypertensive Adult Pakistanis: Inadequate Knowledge among Non-Hypertensive Adult - Huma, Shafqat; Bijrani, Suhail Ahmed; Wassan, Shafi Muhammad; Ahmed, Jamil; Puri, Partab; Puri, Danish (Pakistan Journal of Health Sciences, 2024)
Hypertension was a serious global health issue, with over half of the adults in underdeveloped nations remained undiagnosed. Given its prevalence and associated repercussions, non-hypertensive people continue to have low awareness of hypertension. Objective: To assess Knowledge of hypertension and identify determinants of inadequate Knowledge among non-hypertensive adult Pakistanis. Methods: A cross-sectional survey was conducted from January to May 2024. A sample of 500 non-hypertensive adults was recruited using the snowball sampling technique. The information was gathered using an online survey based on the Hypertension Knowledge-Level Scale (HK-LS). Data analysis was performed using SPSS version 26.0, and chi-square tests were applied to identify determinants of inadequate Knowledge. Results: The research project comprised 265 males (53%) and 235 females (47%), averaging 35.2 years. According to the total knowledge score, only 33.64% of participants had the necessary hypertension information, while 66.36% did not comprehend it. Knowledge about medication compliance, medical care, and hypertension problems was shown to have significant gaps. Age, educational attainment, and a family history of hypertension were among the demographic characteristics that significantly influenced Knowledge (P<0.05). Higher education levels and a family history of hypertension were associated with better knowledge levels among participants. Conclusions: In Pakistan, the non-hypertensive population is largely unaware about hypertension. In order to reduce hypertension and increase awareness, targeted outreach initiatives were necessary. Enhancing health literacy through media, healthcare providers, and family health communication can bridge the knowledge gap.